Identification of a new mlst subtype of cryptosporidium muris from a brown rat (rattus norvegicus) in china - Xuehan LIU; Lei DENG; Zhijun ZHONG; Ziyao ZHOU; Xuefeng YANG; Zhixing AN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
Cryptosporidium muris is a zoonotic protozoan. Characterization of genetic diff erentiation can be exploited to trace the origins of the parasite. A Cryptosporidium isolate from brown rat was obtained by microscopy and genetically characterized. C. muris was identified with minor nucleotide diff erences. Further subtype analysis was performed using a multilocus sequence typing (MLST) tool. At each locus, the C. muris isolate was confirmed to be M12, M4, M1 and M2 subtype, representing as a new MLST subtype. Therefore, the results suggest that there was probably a new source of infection for C. muris in the study region.